Seidel 2008. A Grammar of Yeyi - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Frank Seidel 2008. A Grammar of Yeyi. A Bantu Language of Southern Africa. Rüdiger Köppe Verlag, Köln. 464 pages; 8 Chapters; 57 Tables; 12 Figures; 1341 Illustrations; Index